2012
DOI: 10.1089/ten.tea.2011.0317
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Breast Tubulogenesis Using Extracellular Matrix Composition and Stromal Cells

Abstract: Epithelial-mesenchymal interactions during embryogenesis are critical in defining the phenotype of tissues and organs. The initial elongation of the mammary bud represents a central morphological event requiring extensive epithelial-mesenchymal crosstalk. The precise mechanism orchestrating this outgrowth is still unknown and mostly animal models have been relied upon to explore this process. Highly tunable three-dimensional (3D) culture models are a complementary approach to address the question of phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…8,9 In our current study, we observed that hormonal treatment influenced collagen fiber organization. Quantitative analysis showed that the changes in epithelial organization induced by mammogenic hormones were accompanied by differences in collagen organization.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…8,9 In our current study, we observed that hormonal treatment influenced collagen fiber organization. Quantitative analysis showed that the changes in epithelial organization induced by mammogenic hormones were accompanied by differences in collagen organization.…”
Section: Discussionsupporting
confidence: 54%
“…35 In the conditions of our 3D model, promegestone induced the formation of chain-like structures, which are considered an early step of ductal formation according to Meyer et al 35 The fact that side branching is only partially recapitulated in our model containing epithelial cells and in the model containing epithelial and myoepithelial cells, 34,35 suggests that stromal components such as fibroblasts and/or adipocytes may significantly contribute to this morphogenetic event, as shown in the MCF10A model. 9 We have previously shown that mammary fibroblasts normalize the structures formed by the ER + /PR + MCF7 cells. 12 The stimulation of budding by prolactin was successfully reproduced in our culture model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The hormone-sensitive 3D culture model described herein also allows for the addition of cell types considered of relevance in breast tissue morphogenesis, such as fibroblasts, adipocytes and circulating blood cells 6,8,10 . Finally, testing of hormonal influence on the breast epithelium in this 3D culture model is not limited to endogenous hormones alone.…”
Section: Discussionmentioning
confidence: 99%
“…3D cultures of the mammary gland have helped elucidate many aspects of mammary gland development and neoplasia. However, most of the 3D culture models currently available are unsuitable to study hormone action because the human epithelial cell lines used for the task lack hormone receptor expression 6,7,9 .…”
Section: Introductionmentioning
confidence: 99%